(untitled) (Homoeopathy for All, 2022)
Acidity is a medical condition which is caused due excess production of acid. This acid is produced by the glands of the stomach. Hyperacidity is also called Acid Dyspepsia, which is one of the most common problem. Homoeopathy is a remarkable resource for those dealing with digestive disorders. This article provides an overview of the aetiology, diagnosis, and appropriate general & homoeopathic management of this disorder.